2009
DOI: 10.1111/j.1365-2133.2008.08922.x
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal NK / T-cell lymphoma with cutaneous involvement: ‘nasal’ vs. ‘nasal-type’ subgroups- a retrospective study of 18 patients

Abstract: Extranodal NK/T-cell lymphomas are extremely aggressive regardless of their subgroup. However, the 'nasal-type' NK/T-cell lymphoma was clinically less aggressive, more localized and had a better outcome compared with the other type. Cellulitis and ulcer were the major cutaneous manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 18 publications
6
64
0
2
Order By: Relevance
“…4,18 However, according to other investigators, 1,8,9,19 in our cases the exclusively cutaneous presentation observed in 4 cases was not associated with a better prognosis; all patients died despite the therapy with a 12-month survival rate of 40%. Case 5 had an early lymph node involvement with a very short survival rate.…”
Section: Follow-upsupporting
confidence: 47%
See 1 more Smart Citation
“…4,18 However, according to other investigators, 1,8,9,19 in our cases the exclusively cutaneous presentation observed in 4 cases was not associated with a better prognosis; all patients died despite the therapy with a 12-month survival rate of 40%. Case 5 had an early lymph node involvement with a very short survival rate.…”
Section: Follow-upsupporting
confidence: 47%
“…3 PC-ENK/T-NT lymphoma is rarer; from a review of the literature, only approximately 57 cases are reported and less than 20 cases were in Western countries. [4][5][6][7][8][9][10] However, its real frequency is difficult to establish correctly, because all required data are not always available.…”
Section: Enk/t-nt Lymphoma With Initial Presentation In the Skin Is Kmentioning
confidence: 99%
“…This is the lower incidence of extranasal disease in our hospital. Referral bias is important since nasal and cutaneous disease may be referred initially to orolaryngology or dermatology center [6][7][8][9]. Because of the majority of patients with stage I/II of nasal NK/T lymphoma, RT alone is an important modality.…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug chemotherapy has not been shown to improve outcomes due to the very aggressive nature of this disease. Proposed treatment options include cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) or etoposide, prednisone, vincristine, cyclophosphamide and doxorubicin (EPOCH) [1,4,7] . Unlike nasal NK/T-cell lymphoma, mortality rates have not been well defined for non-nasal aggressive NK/T-cell leukemia/lymphoma but remain exceedingly high, especially within the first 6 weeks to two months, often due to multisystem organ failure [1-3, 5, 6, 9] .…”
Section: Discussionmentioning
confidence: 99%